Implication of Fructans in Health: Immunomodulatory and Antioxidant Mechanisms - Elena Franco-Robles; Mercedes G. López (The Scientific World Journal)
Previous studies have shown that fructans, a soluble dietary fiber, are beneficial to human health and offer a promising approach for the treatment of some diseases. Fructans are nonreducing carbohydrates composed of fructosyl units and terminated by a single glucose molecule. These carbohydrates may be straight or branched with varying degrees of polymerization. Additionally, fructans are resistant to hydrolysis by human digestive enzymes but can be fermented by the colonic microbiota to produce short chain fatty acids (SCFAs), metabolic by-products that possess immunomodulatory activity. The indirect role of fructans in stimulating probiotic growth is one of the mechanisms through which fructans exert their prebiotic activity and improve health or ameliorate disease. However, a more direct mechanism for fructan activity has recently been suggested; fructans may interact with immune cells in the intestinal lumen to modulate immune responses in the body. Fructans are currently being studied for their potential as “ROS scavengers” that benefit intestinal epithelial cells by improving their redox environment. In this review, we discuss recent advances in our understanding of fructans interaction with the intestinal immune system, the gut microbiota, and other components of the intestinal lumen to provide an overview of the mechanisms underlying the effects of fructans on health and disease.